Endotoxin Tolerance Impinges on T Cell Activation and Chemoattraction in Autoimmune Diabetes - Silojärvi, Satu M.; Leino, Linda A. A.; Pöysti, Sakari A.; Hänninen, Arno L. M. (Wiley, 2026)
Gut microbiota may affect the development of autoimmune (type 1) diabetes by differential potency of intestinal species to induce endotoxin tolerance (ET). However, where ET impinges on immune mechanisms underlying autoimmune diabetes is yet incompletely understood. We investigated the effects of lipopolysaccharide (LPS) from E. coli and B. vulgatus, two common intestinal species dominating either in low- or high-incidence countries, on activation and chemoattraction of islet-specific T cells in non-obese diabetic (NOD) mice. Intraperitoneal (i.p.) injection of E. coli LPS induced costimulatory ligands CD40, CD80 and CD86 on both conventional and cross-presenting (XCR1+) dendritic cells (DC) and islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP)-reactive islet-specific T cells in the pancreatic lymph node. In comparison to mice not primed with E. coli LPS or primed with B. vulgatus LPS, the second injection of E. coli LPS lowered the frequency of IGRP-reactive T cells and CD80 expression on DC subsets, as well as CD44 and CD69 activation markers and the CXCR3 chemokine receptor on IGRP-reactive T cells. In islets, expression of chemokine CXCL10 accentuated, and insulitis became more severe in mice primed with B. vulgatus LPS. Our results provide mechanistic insight into how ET affects islet autoimmunity and suggest that physiological exposure to E. coli LPS may benefit in moderating autoimmune diabetes.